Elaborate Mimetic Vocal Displays by Female Superb Lyrebirds - Dalziell, Anastasia H.; Welbergen, Justin A. (Frontiers in Ecology and Evolution, 2016)
Some of the most striking vocalizations in birds are made by males that incorporate vocal mimicry in their sexual displays. Mimetic vocalization in females is largely undescribed, but it is unclear whether this is because of a lack of selection for vocal mimicry in females, or whether the phenomenon has simply been overlooked. These issues are thrown into sharp relief in the superb lyrebird, Menura novaehollandiae, a basal oscine passerine with a lek-like mating system and female uniparental care. The spectacular mimetic song display produced by courting male lyrebirds is a textbook example of a sexually selected trait, but the vocalizations of female lyrebirds are largely unknown. Here, we provide the first analysis of the structure and context of the vocalizations of female lyrebirds. Female lyrebirds were completely silent during courtship; however, females regularly produced sophisticated vocal displays incorporating both lyrebird-specific vocalizations and imitations of sounds within their environment. The structure of female vocalizations varied significantly with context. While foraging, females mostly produced a complex lyrebird-specific song, whereas they gave lyrebird-specific alarm calls most often during nest defense. Within their vocal displays females also included a variety of mimetic vocalizations, including imitations of the calls of dangerous predators, and of alarm calls and song of harmless heterospecifics. Females gave more mimetic vocalizations during nest defense than while foraging, and the types of sounds they imitated varied between these contexts, suggesting that mimetic vocalizations have more than one function. These results are inconsistent with previous portrayals of vocalizations by female lyrebirds as rare, functionless by-products of sexual selection on males. Instead, our results support the hypotheses that complex female vocalizations play a role in nest defense and mediate female-female competition for breeding territories. In sum, this study reveals elaborate female vocal displays in a species widely depicted as an example of sexual selection for male extravagance, and thus highlights the hidden complexity of female vocalizations.